Woodsong - Paulsen, Gary.; Paulsen, Ruth Wright (New York : Bradbury Press, 1991)
For a rugged outdoor man and his family, life in northern Minnesota is a wild experience involving wolves, deer, and the sled dogs that make their way of life possible. Includes an account of the author's first Iditarod, a dogsled race across Alaska.
Illustrated by Ruth Wright Paulsen.
G9
Keywords: Paulsen, Gary -- Homes and haunts -- Minnesota -- Juvenile literature; Paulsen, Gary; Outdoor life -- Minnesota -- Juvenile literature; Dogsledding -- Minnesota -- Juvenile literature; Sled dogs -- Minnesota -- Juvenile literature; Outdoor life -- Minnesota; Sled dogs; Sled dog racing; Minnesota -- Social life and customs -- Juvenile literature; Minnesota -- Biography -- Juvenile literature